Reflective communication to improve problem-solving pathways: Key issues illustrated for an integrated environmental modelling case study. (April 2020) - Zare, Fateme; Guillaume, Joseph H.A.; Jakeman, Anthony J.; Torabi, Oveis
Abstract: The pathway of a modelling project is commonly described as an adaptively adjusted chain of steps at which various decisions are made. Communication and documentation about these decisions are crucial to enabling reflection and adapting the pathway to changing circumstances, such that well-informed planning is required. Project decision making, however, often remains a black box; it is rare to find reporting of dead ends, alternative decisions, and changes in decisions during the project. This paper uses an integrated environmental management case study in Iran to demonstrate the importance of reflective documentation and communication within the pathway. We show how a pathway diagram, incorporating some 14 symbols depicting steps, decision forks, options (selected and alternatives), actions, communication and documentation, can illustrate the role of communication within the project and identify lessons learnt. We also encourage further work on application of agile project management and social science techniques to improve modelling practices. Graphical abstract: Image 1 Highlights: Reflective communication helps to expose the black box of the modelling process. Reflective documentation and communication within projects should be planned in advance. Use of a pathway diagram illustrates the role of communication, identifies lessons learnt. Effective communication along the project pathway is essential to adaptation.